Abnormal circumferential strain measured by echocardiography is present in patients with Shwachman–Diamond syndrome despite normal shortening fraction. Issue 7 (2nd March 2015) - Ryan, Thomas D.; Jefferies, John L.; Chin, Clifford; Sticka, Joshua J.; Taylor, Michael D.; Harris, Richard; Moore, Joan; Goodridge, Erica; Mount, Leann; Bolyard, Audrey A.; Otto, Barbara; Jones, Amanda; et al.
<x xml:space="preserve">Abstract</x> Background Shwachman–Diamond Syndrome (SDS) is an autosomal recessive disorder characterized by bone marrow failure and exocrine pancreatic dysfunction. Heart failure has been described in patients with SDS. Circumferential strain (εcc) is a measure of cardiac performance that may identify dysfunction when standard measures are normal. Procedures Patients with SDS were identified and the echocardiographic database queried. Cardiac anatomy and function were recorded, and εcc was measured retrospectively. Results From 1995–2013, 27 patients with biallelic SBDS mutations confirming the diagnosis of SDS were identified at our institution: 14 had at least one echocardiogram available; 10 underwent HSCT, with echocardiograms available in nine. Ejection fraction (EF) was normal in all 14 patients evaluated; however, εcc was decreased in 4/12 studies prior to HSCT. In two patients, εcc was abnormal both before and after HSCT, in one, εcc changed from normal to abnormal after HSCT, and in one, εcc was normal after HSCT despite being abnormal prior. Echocardiogram reports were also available for six patients in the North American SDS registry, all with normal EF. Conclusions While EF was normal in all patients with SDS, εcc was abnormal in 33% prior to HSCT and 33% of those who had undergone HSCT. This suggests that SDS is associated with systolic dysfunction. Further studies are needed to define the incidence of dysfunction in this group and the progression to heart failure. Pediatr Blood Cancer 2015;62:1228–1231. © 2015 Wiley Periodicals, Inc.